GDP, Time Allocation and Annual Time Worked Per Adult in Central and Eastern European Countries - Jacek Jankiewicz (Economics & Sociology)
When decisions taken in the context of monetary price and monetary income are investigated, economists have naturally tended to focus their attention on the market activities of households. Consequently, a significant portion of the economic decisions that are taken in the non-market sphere have remained overlooked. Thus it has been recognised that it is necessary to take into account the production generated by households in the measurement of economic wealth. The aim of this paper is to analyse differences in the economic activity of selected Central and Eastern Europe societies. The use of traditional statistics and time-use data for this purpose made it possible to compare the conclusions that can be drawn using different sources of information. As the statistical material has been supplemented with time-use data, prior conclusions about creating the economic welfare of these societies needed to be modified. The different allocations of time in the individual societies and the different extents to which household production is substituted by market goods and services have an impact on the level of prosperity of households. The significant differences in terms of compensating for market work with household production which were observed when comparing the daily activity of unemployed men and women, turned out to be a common feature of the analysed populations.